2016
DOI: 10.7448/ias.19.5.20841
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with long‐term antiretroviral therapy attrition among adolescents in rural Uganda: a retrospective study

Abstract: IntroductionAs access to antiretroviral therapy (ART) increases, the success of treatment programmes depends on ensuring high patient retention in HIV care. We examined retention and attrition among adolescents in ART programmes across clinics operated by The AIDS Support Organization (TASO) in Uganda, which has operated both facility- and community-based distribution models of ART delivery since 2004.MethodsUsing a retrospective cohort analysis of patient-level clinical data, we examined attrition and retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
7
32
0
Order By: Relevance
“…A recent study conducted in Canada reported that a quarter of transitioned patients were no longer engaged in care [55]. Although these data are from high-income settings, we may expect similar findings in low-resource settings where report of transition outcomes are less common [48,50]. Descriptions of ongoing research efforts to capture transition outcomes in African settings and how they differ from high- and middle-income settings are necessary in order to identify key steps in the HIV cascade for interventions.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…A recent study conducted in Canada reported that a quarter of transitioned patients were no longer engaged in care [55]. Although these data are from high-income settings, we may expect similar findings in low-resource settings where report of transition outcomes are less common [48,50]. Descriptions of ongoing research efforts to capture transition outcomes in African settings and how they differ from high- and middle-income settings are necessary in order to identify key steps in the HIV cascade for interventions.…”
Section: Discussionmentioning
confidence: 62%
“…Support groups and greater involvement of adolescent healthcare providers have been suggested by healthcare providers themselves to facilitate transition [22,30]. Teen clinics have also been found in a small number of studies to improve retention compared to the standard model of care which is the most prevalent [48,50]. Although these youth-focused health services may improve their retention in HIV care, it is difficult to generalize study results due to their limited numbers, sample sizes, and short follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Uganda, Okoboi et al . describe how retention in care was better among younger adolescents (aged 10–14 years) than older adolescents, adolescents who initiated ART in earlier years of the programme when it had a stronger community focus and adolescents who had higher CD4 counts at ART initiation [20]. …”
mentioning
confidence: 99%